Heterogeneous exporters: Qualitative differences and qualitative similarities - Camila Casas; Federico J. Díez; Alejandra González (Federal Reserve Bank of Boston, 2017)
We combine two detailed datasets on Colombian manufacturing firms and document several stylized facts on exporter heterogeneity of total factor productivity (TFP) and export-market orientation, refining some previously known facts and unveiling some new others. We first show that the exporter productivity premium is remarkably robust across the methodologies used to recover TFP. We then document that the most productive exporters are those that export (1) a higher share of their total production, (2) to a larger number of countries, (3) to destinations lessfrequently reached by other exporters, (4) a larger number of products, and (5) with greater frequency and stability. In contrast, (6) the type of destination country or (7) the type of exported product has no significant effect on exporter productivity differences. These facts are robust to alternative definitions and specifications and can provide useful guidelines for policy makers.
Keywords: D24; F14; L60; 330; productivity premium; export intensity; export extensive margins